Mixed Epithelial and Stromal Tumor of the Kidney With Elevated Serum Level of Cancer Antigen 125 - Chih-Hsin Liu; Chia-Cheng Yu; Chao-Ren Chang; Tony T. Wu; Jong-Khing Huang (Journal of the Formosan Medical Association, 2011)
Mixed epithelial and stromal tumor of the kidney is a newly categorized lesion, with few reported cases. We report a rare case of a 45-year-old woman with a palpable abdominal mass and elevated serum level of serum cancer antigen 125, who was not receiving hormones or contraceptive agents. Abdominal magnetic resonance imaging revealed a large multilocular cystic tumor that arose in the left central kidney. Nephrectomy was performed under the initial impression of cystic renal cell carcinoma; however, a diagnosis of mixed epithelial and stromal tumor was confirmed according to pathological and immunohistochemical findings. Serum level of cancer antigen 125 returned to normal after 1 month postoperatively and no recurrence was found in the following 18 months.